Influence of Microstructure on the Dynamic Behaviour of Polyurethane Foam with Various Densities - Boumdouha, Noureddine; Louar, Mohamed Abderaouf (Journal of Basic & Applied Sciences, 2023)
Polyurethane foam is reinforced with varying proportions of metal loads and other components to increase shock absorption and mechanical impact. The main objective is to develop high-performance polymeric materials based on polyurethane foam developed with different compositions and specific densities. We monitor the growth distances and temperatures of the polyurethane foam in time to reach the optimum formulations. We conduct static compression tests and investigate the effect of drop weight on the deformation of polyurethane foam structures by dropping a weight from a specified height. Dynamic collisions cause deformations of the polyurethane foam structure. After investigating the low weight, we found that polyurethane foams have a good absorption coefficient at certain frequencies. Dynamic stress-strain response curves are used to characterize different stress rates. High-stress levels and similar strains indicate a high resistance to shock. We follow the evolution of microstructure structures by scanning electron microscopy (SEM) to observe deformation and fracture behavior with reversibility and recovery.